Development of the fetal myocardium and changes in myocardial fibers orientation - Biagio Castaldi; Marny Fedrigo; Daniela P. Boso; Irene Cattapan; Elena De Filippi; Francesca M. Susin; Paolo Peruzzo; Giulia Comunale; Paola Veronese; Ornella Milanesi; Annalisa Angelini; Giovanni Di Salvo (PLoS ONE, 2025)
Background and aims The mature left ventricular myocardium is arranged in a complex three-dimensional network of fibers that form a counterclockwise helix in the endocardial layer and a clockwise helix in the epicardial layer. There are no data in the literature on the development of left ventricular myocardium during the fetal life. The aims of this paper were to study the physiological maturation steps of the LV myocardium in fetuses from 17 to 40 gestational weeks, by means of speckle tracking applied to the endocardial and epicardial aspect of the left ventricle, and, to confirm our finds, through the histologic study of the myocardium of demised fetuses. Methods and results We studied longitudinal endocardial and epicardial strain by echocardiography in 105 fetuses. Twenty non-diseased fetal hearts from autopsies were selected to assess the layer thickness and cardiac fiber orientation in relation to gestational age. Echocardiography showed a progressive increasing of epicardial/endocardial longitudinal strain ratio with gestational age (r=0.51; p<0.0001). The strain rate E/A ratio increased over time (r=0.27; p=0.018). Histological data revealed that during the same gestational period, the proportion of the epicardial layer increased fourfold, the mesocardiac layer decreased and the endocardial layer remained stable. We found an excellent correlation between the epicardial to endocardial strain ratio and epicardial to endocardial wall thickness (r=0.950, p<0.001). Conclusions Left ventricular myocardium maturation begins early during fetal life. As the fetus develops, both the relative tissue volume and peak systolic strain rates shift together from the endocardium towards the epicardium. It is a slow process, completed late in fetal life.